2022
DOI: 10.1155/2022/1094771
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Ethanol Extract of Red Okra Pods (Abelmoschus esculentus (L.) Moench) to Inhibit Cervical Cancer Cells Growth through Cell Cycle-Associated Oncogenes

Abstract: This study aims to evaluate the potency of ethanol extract of red okra pods (EEROP) in inhibiting growth of cervical cancer cells through repression of the cell cycle-associated oncogenes. The EEROP treatment was given to HeLa cells cultured with RPMI medium and incubated at 37°C with 5% CO2. The MTT method was used to measure HeLa cell growth and IC50 values. The mRNA levels of the three cell cycle-associated oncogenes (MYC, TYMS, and MDM2) were evaluated by qRT-PCR to determine the effect of EEROP treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Extracts from red okra obtained through various extraction methods can also play an essential role in preventing and treating many diseases. According to several studies, ethanol extract of red okra pods has been reported to exhibit anticancer activity [42,43], and n-hexane extract has been reported to show a protective effect against liver damage [5]. However, these studies did not standardize the extraction method and ingredients, and, in particular, there are no studies on pectin from red okra.…”
Section: Discussionmentioning
confidence: 99%
“…Extracts from red okra obtained through various extraction methods can also play an essential role in preventing and treating many diseases. According to several studies, ethanol extract of red okra pods has been reported to exhibit anticancer activity [42,43], and n-hexane extract has been reported to show a protective effect against liver damage [5]. However, these studies did not standardize the extraction method and ingredients, and, in particular, there are no studies on pectin from red okra.…”
Section: Discussionmentioning
confidence: 99%